Impacto de la separacion de los padres en el desarrollo social de hijos/as en etapa de niñez intermedia, demuna - el porvenir . año 2014 - Vasquez Lujan, Carla Yessenia (2015)
This study is guided by the Theory of Social Development, which facilitates the understanding of the process of socialization of children in middle childhood stage and how it affects the separation of parents in the learning process of the above. The importance and contribution of the study is to demonstrate that there is good consequences that impede social development of children of parents who are in the process of separation and assume parental responsibility based on the care and communication with their children. It has been sampled to 33 children in middle childhood stage (6-12 years), children of separated parents registered with the Defensoría Municipal del Niño, Niña y Adolescente - DEMUNA district El Porvenir. The results led to concluding that the separation of parents negatively affects the social development of their children, related to increasing indifference to the problems of family and / or friends (from 33% to 39%). Lost respect for their elders, from 31% to 67% use nicknames, especially to their parents. Improper handling of pulses from 19% to 57% children responding to react before thinking about what they are doing and self-consciousness to express their feelings for their parents